2019
DOI: 10.1038/s41559-019-0998-8
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation innovation through complex hybridization of wild and domesticated yeasts

Abstract: The most common fermented beverage, lager beer, is produced by interspecies hybrids of the brewing yeast Saccharomyces cerevisiae and its wild relative Saccharomyces eubayanus. Lagerbrewing yeasts are not the only example of hybrid vigor or heterosis in yeasts, but the full breadth of interspecies hybrids associated with human fermentations has received less attention. Here we present a comprehensive genomic analysis of 122 Saccharomyces hybrids and introgressed strains. These strains arose from hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 98 publications
(64 reference statements)
5
114
0
Order By: Relevance
“…Notably, all models agree that Europe is climatically a prime location for S. eubayanus (S12C Fig), but no pure isolates have ever been found there, only hybrids with S. uvarum, S. cerevisiae, or hybrids with even more parents [11,13]. These hybrids with complex ancestries have been found in numerous fermentation environments, suggesting that pure S. eubayanus once existed, or still exists at low abundance or in obscure locations, in Europe.…”
Section: Plos Geneticsmentioning
confidence: 74%
See 1 more Smart Citation
“…Notably, all models agree that Europe is climatically a prime location for S. eubayanus (S12C Fig), but no pure isolates have ever been found there, only hybrids with S. uvarum, S. cerevisiae, or hybrids with even more parents [11,13]. These hybrids with complex ancestries have been found in numerous fermentation environments, suggesting that pure S. eubayanus once existed, or still exists at low abundance or in obscure locations, in Europe.…”
Section: Plos Geneticsmentioning
confidence: 74%
“…Pure isolates of their more distant relative Saccharomyces eubayanus have only ever been isolated from wild environments; yet, hybridizations between S. cerevisiae and S. eubayanus were key innovations that enabled cold fermentation and lager brewing [7][8][9][10]. Other hybrids with contributions from S. eubayanus have been isolated from industrial environments [11][12][13][14], indicating that this species has long been playing a role in shaping many fermented products. This association with both natural and domesticated environments makes S. eubayanus an excellent model where both wild diversity and domestication can be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequencing revealed that the S. cerevisiae parent strain of this hybrid belonged to the 'Beer 2' lineage. A genetically very similar hybrid, WLP351, was also recently identified, and it is possible that it is the same strain (Langdon et al 2019). STA1 is also present in the S. cerevisiae sub-genomes of various S. cerevisiae × Saccharomyces kudriavzevii hybrids that have been isolated from beer .…”
Section: Functional Role Of Sta1mentioning
confidence: 99%
“…As a heritage, they could be used to strengthen the local character of wines produced with them and thus contribute to the terroir of these wines [19][20][21]. To be useful as a breeding stock, these old strains need to be characterized in more detail, preferably including their genomes [22,23]. In our study, the yeast with the most pronounced flavor production capability of alcohols and esters was the S. cerevisiae strain Rüdesheimer Hinterhaus 1893 ('Hinterhaus' refers to backyard).…”
Section: Discussionmentioning
confidence: 99%